2021
DOI: 10.3390/ma14195722
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Critical Dynamic Stress and Accumulative Plastic Strain of an Unbound Granular Material Based on Cyclic Triaxial Tests

Abstract: Critical dynamic stress (σcri) and accumulative plastic strain (εp) are primary indicators regarding the dynamic stability of unbound granular materials (UGMs). This study aims to seek an effective method to evaluate the dynamic stability of UGMs used in railway subgrades. First, the dynamic characteristics of an UGM used in railway subgrade bed construction were investigated by performing a series of large-scale cyclic triaxial tests, with the results showing that εp versus cycle number (N) curves can be cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The accumulative plastic strain-time curves of geotechnical materials term alternating load can be categorized into three types [40]: (1) steady curv curve; (3) failure curve, as shown in Figure 4a. The dynamic stress that make lative strain-time curve evolve into a critical curve is called critical dynam and accumulative strain-time curves evolve into steady or failure curves, d whether the dynamic stress is lower or higher than 𝜎 .…”
Section: Deformation Characteristics Of Clay Under Alternating Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulative plastic strain-time curves of geotechnical materials term alternating load can be categorized into three types [40]: (1) steady curv curve; (3) failure curve, as shown in Figure 4a. The dynamic stress that make lative strain-time curve evolve into a critical curve is called critical dynam and accumulative strain-time curves evolve into steady or failure curves, d whether the dynamic stress is lower or higher than 𝜎 .…”
Section: Deformation Characteristics Of Clay Under Alternating Loadmentioning
confidence: 99%
“…The accumulative plastic strain-time curves of geotechnical materials under long-term alternating load can be categorized into three types [40]: (1) steady curve; (2) critical curve;…”
Section: Deformation Characteristics Of Clay Under Alternating Loadmentioning
confidence: 99%
“…While much documentation exists regarding the need to consider the viscoelastic behavior of asphalt concrete (AC) mixtures more representatively [7][8][9], the actual behavior of the unbound granular materials located in the base and sub-base layers is usually overlooked. Multiple studies over the years have recognized the significance of the behavior of unbound granular materials [10][11][12], which is normally nonlinear elastic. Other studies have additionally focused on the base material Designs 2023, 7, 142 2 of 14 cross-anisotropy [13][14][15], as well as on the joint modeling of the unbound materials' nonlinear and anisotropic behavior [16][17][18][19][20].…”
Section: Introduction 1overviewmentioning
confidence: 99%
“…Consistent research interests are observed that investigate correlations between inputs during the design of the unbound materials and pavement performance. To this end, the use of finite element method (FEM) tools is an efficient approach to investigate pavement responses' sensitivity with respect to variations in several geometric or material parameters that affect pavement design [10,22,23]. Considering that during a pavement's construction process, deviations between the design and the as-built values of either the pavement's geometric or material properties frequently occur, leading to additional short-term or long-term costs for the road agencies, it always remains challenging to access efficient tools to accurately predict the impact that such deviations may potentially have on future pavement responses.…”
Section: Introduction 1overviewmentioning
confidence: 99%
“…However, increasing train speeds and axle loads can inevitably lead to an increase in the load frequencies and magnitudes acting on the railway subgrade and accelerate the micro-structural damage of the subgrade. Consequently, a series of possible railroad subgrade diseases, such as unacceptable settlement, subgrade slope instability, cracking in the shoulder section, and ballast pockets would develop and seriously hamper the operational safety and efficiency of existing railways [ 1 , 2 ]. These diseases are closely related to a poor stress state of the subgrade soil and a lack of lateral deformation constraint of the subgrade slope.…”
Section: Introductionmentioning
confidence: 99%